Genetic Cancer Risk Assessment for Breast Cancer in Latin America - Chavarri-Guerra, Yanin (Rev Invest Clin, 2017)
In Latin America, breast cancer is the most common malignancy in women, and limited available data suggest that up to 15% of all breast cancer cases in the region are hereditary. Genetic cancer risk assessment and counseling is a critical component of the appropriate clinical care of patients with hereditary breast cancer and their families. Unfortunately, genetic services are underdeveloped across Latin America, and access to genetic testing and counseling is very scarce in the region. Barriers contributing to the access to genetic care are high cost and lack of insurance coverage for genetic tests, insufficient oncogenetics training or expertise, nonexistence of genetic counseling as a clinical discipline and lack of supportive healthcare policies. In this review, we highlight relevant initiatives undertaken in several Latin American countries aimed at creating genetic cancer risk assessment programs. Additionally, we present a review of the scientific literature on the current status of breast cancer genomics in Latin America, with specific emphasis on demographic indicators, access to cancer genetic care, training and strategies to improve outcomes and international collaborations.